Muscle Transcriptomics Shows Overexpression of Cadherin 1 in Inclusion Body Myositis. Issue 3 (11th February 2022) - Ikenaga, Chiseko; Date, Hidetoshi; Kanagawa, Motoi; Mitsui, Jun; Ishiura, Hiroyuki; Yoshimura, Jun; Pinal‐Fernandez, Iago; Mammen, Andrew L.; Lloyd, Thomas E.; Tsuji, Shoji; Shimizu, Jun; Toda, Tatsushi; et al.
Abstract : Objective: This study aimed to elucidate the molecular features of inclusion body myositis (IBM). Methods: We performed RNA sequencing analysis of muscle biopsy samples from 67 participants, consisting of 58 myositis patients with the pathological finding of CD8‐positive T cells invading non‐necrotic muscle fibers expressing major histocompatibility complex class I (43 IBM, 6 polymyositis, and 9 unclassifiable myositis), and 9 controls. Results: Cluster analysis, principal component analysis, and pathway analysis showed that differentially expressed genes and pathways identified in IBM and polymyositis were mostly comparable. However, pathways related to cell adhesion molecules were upregulated in IBM as compared with polymyositis and controls ( p  < 0.01). Notably, CDH1, which encodes the epidermal cell junction protein cadherin 1, was overexpressed in the muscles of IBM, which was validated by another RNA sequencing dataset from previous publications. Western blotting confirmed the presence of mature cadherin 1 protein in the muscles of IBM. Immunohistochemical staining confirmed the positivity for anti‐cadherin 1 antibody in the muscles of IBM, whereas there was no muscle fiber positive for anti‐cadherin 1 antibody in immune‐mediated necrotizing myopathy, antisynthetase syndrome, and controls. The fibers stained with anti‐cadherin 1 antibody did not have rimmed vacuoles or abnormal protein accumulation. Experimental skeletal muscle regeneration and differentiation systems showed that CDH1 is expressed during skeletal muscle regeneration and differentiation. Interpretation: CDH1 was detected as a differentially expressed gene, and immunohistochemistry showed that cadherin 1 exists in the muscles of IBM, whereas it was rarely seen in those of other idiopathic inflammatory myopathies. Cadherin 1 upregulation in muscle could provide a valuable clue to the pathological mechanisms of IBM. ANN NEUROL 2022;91:317–328